Management of Geographic Tongue with Individualized Homeopathy: An Evidence-Based Case Report - Saklani, Nitin Kumar (Homœopathic Links, 2024)
Geographic tongue, also known as benign migratory glossitis, is a common and benign condition characterized by distinct features on the tongue's surface. Typically, it affects the tip, lateral borders, and dorsum of the tongue, with occasional extension to the ventral surface. Indeed, geographic tongue commonly starts in childhood and has a global prevalence estimated at around 1 to 2.5% of the general population. In the pediatric population, the prevalence ranges from 0.37 to 14.3%, indicating that it can vary significantly among different age groups. The age group of 20 to 29 years seems to have the highest prevalence, with approximately 39.4% of individuals affected by geographic tongue. This suggests a peak incidence during early adulthood. This case report explores the potential benefits of homeopathic medicines in management of geographic tongue. A 17-year-old adolescent girl experiencing whitish discoloration of the tongue accompanied by intense burning sensation with history of recurrent tonsillitis and increased sweating in her palms and soles since early childhood presented in the OPD of Regional Research Institute for Homoeopathy, Shimla. Upon examination of her oral cavity, white patches were observed on her tongue, which did not resolve despite trying various medications. The primary diagnosis was geographic tongue, confirmed by physical examination. Following homeopathic treatment, the patient experienced marked improvement in symptomatology, including relief from the burning sensation, and the lesion from the tongue completely disappeared. This evidence-based case report highlights the potential beneficial role of homeopathy in the treatment of geographic tongue.
Keywords: case report; homeopathy; individualized homeopathic medicine; geographic tongue